2000
DOI: 10.1097/00000539-200012000-00023
|View full text |Cite
|
Sign up to set email alerts
|

The Lack of Systematic Month-to-Month Variation Over One-Year Periods in Ambulatory Surgery Caseload —Application to Anesthesia Staffing

Abstract: Anesthesia groups forecast future workload so that staffing and future hiring can be adjusted. Statistical methods have been developed to estimate the number of anesthesia providers needed to minimize labor costs during regularly scheduled hours, second-shifts, and weekends. These methods are simple, in that they assume that, on this medium-range (11-mo) basis, workload varies irregularly around a mean workload. To test whether this assumption is likely to hold for many anesthesia groups nationwide, raw data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 7 publications
0
18
1
Order By: Relevance
“…4,5 In the long run, if the distribution of OR labor costs and surgical demand (both in terms of case volume and procedure type) replicates the historical distributions used to develop the initial staffing parameters, OR efficiency will be maximized. Both the monthly aggregated surgical volume 6 and the individual surgical subspecialty's 4-week volume 7 can be fairly accurately predicted using statistical methods, and these can be used for planning monthly staffing. However, variability in surgical case volume in the short term (weekly and daily time scales) provides an additional opportunity to extract further improvements in matching OR costs to revenue opportunities.…”
Section: -3mentioning
confidence: 99%
“…4,5 In the long run, if the distribution of OR labor costs and surgical demand (both in terms of case volume and procedure type) replicates the historical distributions used to develop the initial staffing parameters, OR efficiency will be maximized. Both the monthly aggregated surgical volume 6 and the individual surgical subspecialty's 4-week volume 7 can be fairly accurately predicted using statistical methods, and these can be used for planning monthly staffing. However, variability in surgical case volume in the short term (weekly and daily time scales) provides an additional opportunity to extract further improvements in matching OR costs to revenue opportunities.…”
Section: -3mentioning
confidence: 99%
“…16 If workloads of all pediatric otolaryngologists varied seasonally (e.g., because young children develop more ear infections during the winter months), 16 a change in the caseload of one surgeon would predict changes in the caseloads of the other pediatric otolaryngologists. Nevertheless, prior analyses from two hospitals suggested that the preceding example 16 using national data does not apply to individual hospitals.…”
Section: Statistical Independence Of Surgeons' Caseloadsmentioning
confidence: 99%
“…16 If workloads of all pediatric otolaryngologists varied seasonally (e.g., because young children develop more ear infections during the winter months), 16 a change in the caseload of one surgeon would predict changes in the caseloads of the other pediatric otolaryngologists. Nevertheless, prior analyses from two hospitals suggested that the preceding example 16 using national data does not apply to individual hospitals. 1,10 Hypothesis #2 During relevant (one year) time periods, caseloads of surgeons are uncorrelated or correlated so weakly as to be managerially irrelevant for predicting the caseload of an individual surgeon.…”
Section: Statistical Independence Of Surgeons' Caseloadsmentioning
confidence: 99%
“…21 However, all the references, cited above, limited consideration to individual facilities (i.e., each facility independently planned staffing and performed case scheduling). Findings may not apply to health systems with the potential to move cases among the various affiliated hospitals.…”
mentioning
confidence: 99%